STRATEGI MANAJEMEN HUMAS DALAM MENINGKATKAN JUMLAH PESERTA DIDIK BARU DI SMP IT AL-UTSAIMIN - Muhammad Arif; Ermansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the Public Relations (PR) management strategy in increasing the number of new students at SMP IT Al-Utsaimin, analyze its supporting and inhibiting factors. Employing a qualitative approach with a descriptive research design, data were collected through in-depth interviews, observation, and documentation studies. The results indicate that the PR management strategy is implemented through the optimization of digital media (Facebook, Instagram, WhatsApp), direct promotion via school activities (open houses, competitions, public religious gatherings), and collaboration with community leaders and alumni. These activities are accompanied by periodic evaluations. Supporting factors include solid cooperation among the principal, foundation, staff, and the surrounding community. Conversely, the inhibiting factors involve limited human resource competencies in digital marketing, promotional budget constraints, and increasingly competitive inter-school rivalry. As a follow-up, it is recommended to improve human resource competencies, strengthen coordination among stakeholders, and develop targeted digital strategies to maintain public trust and sustain the continuous increase in new student enrollment.